(untitled) (Research, Society and Development, 2022)
The metabolic syndrome (MetS) is a complex of risk factors for cardiovascular disease and its incidence has increased globally, causing this condition to be currently a global public health problem. It was estimated that 20 to 35% of the world’s population has MetS. However, the global prevalence ratios vary enormously, due mainly to social and economic discrepancies. Despite the importance of MetS in the context of metabolic and cardiovascular disease, studies that described the prevalence of MetS and its determinants among rural and vulnerable populations worldwide. In this study, we aimed to determine the MetS prevalence and associated risk factors in a riverside population living in Pantanal biome from Mato Grosso do Sul in Brazil, that has difficulties in accessing health services. This investigation is a retrospective cross-sectional study conducted from March 2010 to July 2016 in adult individuals (aged 18 years or older)) from riverside community of Passo do Lontra. MetS was defined according to NCEP/ATP III, 2001criteria. A total of 81 adult individuals, being 36 (44.4%) females and 45 (55.6%) males were enrolled. The overall MetS prevalence was 40.7% (33/81) with no gender difference. About the risk factors analysis, higher levels of BMI, uric acid, non-HDL, VLDL cholesterol and obesity among adults led to higher chances of developing the syndrome. These findings provide important evidence on the MetS prevalence as a public health problem, particularly for obese, dyslipidemic and hyperuricemic individuals. Our results reinforce an alarming public health trend.